Genomic epidemiology of Lineage 4 Mycobacterium tuberculosis subpopulations in New York city and New Jersey, 1999–2009. (December 2016) - Brown, Tyler; Narechania, Apurva; Walker, John; Planet, Paul; Bifani, Pablo; Kolokotronis, Sergios-Orestis; Kreiswirth, Barry; Mathema, Barun
Abstract Background Whole genome sequencing (WGS) has rapidly become an important research tool in tuberculosis epidemiology and is likely to replace many existing methods in public health microbiology in the near future. WGS-based methods may be particularly useful in areas with less diverseMycobacterium tuberculosis populations, such as New York City, where conventional genotyping is often uninformative and field epidemiology often difficult. This study applies four candidate strategies for WGS-based identification of emergingM. tuberculosis subpopulations, employing both phylogenomic and population genetics methods. Results M. tuberculosis subpopulations in New York City and New Jersey can be distinguished via phylogenomic reconstruction, evidence of demographic expansion and subpopulation-specific signatures of selection, and by determination of subgroup-defining nucleotide substitutions. These methods identified known historical outbreak clusters and previously unidentified subpopulations within relatively monomorphicM. tuberculosis endemic clone groups. Neutrality statistics based on the site frequency spectrum were less useful for identifyingM. tuberculosis subpopulations, likely due to the low levels of informative genetic variation in recently diverged isolate groups. In addition, we observed that isolates from New York City endemic clone groups have acquired multiple non-synonymous SNPs in virulence- and growth-associated pathways, and relatively few mutations in drug resistance-associated genes, suggesting that overall pathoadaptive fitness, rather than the acquisition of drug resistance mutations, has played a central role in the evolutionary history and epidemiology ofM. tuberculosis subpopulations in New York City. Conclusions Our results demonstrate that some but not all WGS-based methods are useful for detection of emergingM. tuberculosis clone groups, and support the use of phylogenomic reconstruction in routine tuberculosis laboratory surveillance, particularly in areas with relatively less diverseM. tuberculosis populations. Our study also supports the use of wider-reaching phylogenomic and population genomic methods in tuberculosis public health practice, which can support tuberculosis control activities by identifying genetic polymorphisms contributing to epidemiological success in localM. tuberculosis populations and possibly explain why certain isolate groups are apparently more successful in specific host populations.